2020
DOI: 10.1002/cphc.202000629
|View full text |Cite
|
Sign up to set email alerts
|

Towards Accurate Predictions of Proton NMR Spectroscopic Parameters in Molecular Solids

Abstract: The factors contributing to the accuracy of quantum‐chemical calculations for the prediction of proton NMR chemical shifts in molecular solids are systematically investigated. Proton chemical shifts of six solid amino acids with hydrogen atoms in various bonding environments (CH, CH2, CH3, OH, SH and NH3) were determined experimentally using ultra‐fast magic‐angle spinning and proton‐detected 2D NMR experiments. The standard DFT method commonly used for the calculations of NMR parameters of solids is shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“… b Maximum error and the corresponding hydrogen atom. c GIPAW values from the work of Dračínský et al 18 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… b Maximum error and the corresponding hydrogen atom. c GIPAW values from the work of Dračínský et al 18 …”
Section: Resultsmentioning
confidence: 99%
“… a Experimental values from ref ( 18 ). b Values calculated using the scheme described in Section 2.2 with pcSseg-3 and pcSseg-2 basis sets for QM1 and QM2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently investigated the factors contributing to the accuracy of the chemicalshift predictions of hydrogen nuclei in molecular solids and observed that the GGAcalculated proton chemical shifts deviated up to 1.5 ppm from the experiment, with the largest deviation observed for a hydrogen atom attached to sulfur, which has been explained by the neglect of relativistic effects in the calculations [21]. Furthermore, when hydrogen atoms are involved in strong hydrogen bonds, nuclear quantum effects (NQEs), such as proton delocalization and tunneling, may become important for the predictions of nuclear shielding [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%